HIV transmission in discordant couples in Africa in the context of antiretroviral therapy availability. (31st July 2018) - Woodson, Evonne; Goldberg, Alec; Michelo, Clive; Basu, Debby; Tao, Sijia; Schinazi, Raymond; Jiang, Yong; Kilembe, William; Karita, Etienne; Allen, Susan; Hunter, Eric
Abstract : Objective: The study aims to understand the basis of continued HIV-1 transmission in Zambian and Rwandan HIV-1-discordant couples in the context of antiretroviral therapy (ART). Design: We identified nine Zambian and seven Rwandan acutely infected, epidemiologically-linked couples from government couples' voluntary counseling and testing (CVCT) clinics where transmitting partners reported being on ART near the time of transmission. Methods: We quantified viral load and plasma antiretroviral drug concentrations near the time of transmission and used these as surrogate measures for adherence. We also sequenced the polymerase gene from both donor and recipient partners to determine the presence of drug resistance mutations (DRMs). Results: In Zambia, all transmitting partners had detectable viral loads, and 8/9 were not on therapeutic antiretroviral regimens. In the remaining couple, despite being on a therapeutic regimen, DRMs were present and transmitted. In Rwanda, although six of seven transmitting partners had detectable viral loads, therapeutic levels of antiretroviral drugs were detected in four of seven, but were accompanied by DRMs. In the remaining three couples, either no antiretrovirals or subtherapeutic regimens were detected. Conclusions: A reduction of ART effectiveness in nontrial settings was associated with lack of antiretrovirals in plasma and detectable viral load, and also drug resistance. In Zambia, where CVCT is not widely implemented, inconsistent adherence was high in couples unaware of their HIV discordance. In Rwanda, where CVCT is deployed country-wide, virologic failure was associated with drug resistance and subsequent transmission. Together, these findings suggest that increasing ART availability in resource-limited settings without risk reduction strategies that promote adherence may not be sufficient to control the HIV epidemic in the post-ART era. Abstract : Supplemental Digital Content is available in the text